Pengaruh Persepsi Masyarakat tentang Perbankan Syariah terhadap Minat Menabung di Bank BNI Syariah KCP Kepanjen : (Studi Kasus pada Mahasiswa Unira Malang Angkatan 2017-2018) - Fi’ika Tiasari; Hilda Sanjayawati (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2022)
In Indonesia, there are two types of banks, namely conventional banks and Islamic banks. It is undeniable that public perception will have an impact on the progress of Islamic banks and will also encourage people to choose and use Islamic bank products. The purpose of this study was to determine and analyze the influence of public perceptions of Islamic banking on interest in saving at BNI Syariah banks. The population used in this study were students of UNIRA Malang. With a total of 1085 students. The sample used as the object in this study were 90 students. Sample collection technique is done by using Random Sampling Method (RandomSampling),the technique of making members of the sample population was randomly without regard to strata that exist within that population. The data analysis technique was carried out using a simple linear regression method with statistical tests first. The statistical test consists of the t test, and the coefficient of determination (R2). Data processing in this study usingtools SPSS 16. Based on the results of the research, the results of the t test indicate that the perception variable has a positive and significant effect on people's interest in saving. The value of tcount is greater than ttable (13.301 > 1.98698). While the result of determination of R2 is 0.668. the perception variable has an influence of 66.8% on the variable of interest in saving while the remaining 33.2% is influenced by other variables not mentioned in this study